The Profile of Students' English Linguistic Intelligence: A Case Study at SMP Islam De Green Camp Tanjungpinang - lisa anriani; Dewi Nopita; Dewi Murni (English Language Education Study Program Universitas Maritim Raja Ali Haji, 2021)
This study aimed to know how is the profile of students’ English linguistic intelligence of rhetoric at SMP Islam De Green Camp Tanjungpinang. The subject in this research is the eighth grade that consisted of 21 female students. This study is based on Gardner’s theory (1998). A research design in this research is descriptive qualitative research with analysis technique. The setting of place in this research is at SMP Islam De Green Camp Tanjungpinang. The instruments in collecting the data are interviews and speaking tests. Based on the instruments, the researcher assesses students’ answers by a rubric that consisted of grammar, pronunciation, vocabulary, fluency, and comprehension. The result shows that the total score is 61.9 and from the criteria of the rhetoric on speaking, the students’ English linguistic intelligence of rhetoric at SMP Islam De Green Camp Tanjungpinang is good.